Water demands of permitted and unpermitted cannabis cultivation in Northern California. (17th February 2023) - Dillis, Christopher; Butsic, Van; Georgakakos, Phillip; Portugal, Elijah; Grantham, Theodore E
Abstract: Illicit water use for irrigated agriculture can have substantial impacts on the environment and complicates water management decision-making. Water demand for illicit cannabis farming in California has long been considered a threat to watershed health, yet an accounting of cannabis irrigation has remained elusive, thereby impeding effective water policy for the state's nascent legal cannabis industry. Using data obtained from both permitted and unpermitted cultivation operations, the current study applies novel water-use models to cannabis farms in Northern California to estimate their cumulative and relative water footprints. Our results indicated substantial variation in total water extraction volumes for cannabis farming between watersheds and that most cannabis water use was concentrated in a subset of watersheds, rather than evenly spread across the landscape. Water extraction volumes for unpermitted cannabis were consistently greater than permitted cannabis in the dry season, when streams are most vulnerable to impacts from water diversions. Results from scenario modeling exercises indicated that if all existing unpermitted farms were to become permitted and comply with regulations that prohibit surface water diversions in the dry season, nearly one third (34 of 115) of the study watersheds would experience a 50% reduction in dry season water extraction. In comparison, modest expansion of off-stream storage by all cannabis farms could reduce dry season extraction by 50% or greater in more than three quarters (96 of 115) of study watersheds. Combining diversion limits with enhanced storage could achieve dry season extraction reductions of 50% or greater in 100 of 115 watersheds. Our findings suggest that efforts to address the environmental impacts of unpermitted cultivation should focus on watersheds with greatest water demands and that programs that support expansion of off-stream storage can be helpful for reducing pressures on the environment and facilitating the transition of unpermitted farms to the regulated market.